A Patient-Centered Evaluation of Meaningful Change on the 32-Item Motor Function Measure in Spinal Muscular Atrophy Using Qualitative and Quantitative Data - Duong, Tina; Staunton, Hannah; Braid, Jessica; Barriere, Aurelie; Trzaskoma, Ben; Gao, Ling; Willgoss, Tom; Cruz, Rosangel; Gusset, Nicole; Gorni, Ksenija; Randhawa, Sharan; Yang, Lida; et al. (Frontiers in Neurology, 2022)
The 32-item Motor Function Measure (MFM32) is an assessment of motor function used to evaluate fine and gross motor ability in patients with neuromuscular disorders, including spinal muscular atrophy (SMA). Reliability and validity of the MFM32 has been documented in individuals with SMA. Through semi-structured qualitative interviews (N=40) and an online survey in eight countries (N=217) with individuals with Types 2 and 3 SMA aged 2–59 years old and caregivers, the meaning of changes on a patient-friendly version of the MFM32 was explored. In an independent analysis of clinical trial data, anchor- and distribution-based analyses were conducted in a sample of Type 2 and non-ambulant Type 3 SMA individuals to estimate patient-centered quantitative MFM32 meaningful change thresholds. The results from this study demonstrate that, based on patient and caregiver insights, maintaining functional ability as assessed by a patient-friendly version of the MFM32 is an important outcome. Quantitative analyses using multiple anchors (median age range of 5-8 years old across anchor groups) indicated that approximately 3-points improvement in MFM32 total score represents meaningful change at the individual patient-level. Future research is needed to explore quantitative differences in meaningful change on the MFM32 based on age and functional subgroups.